Navigating the Impact: Turkey's Foreign Policy Post-2018 US Sanctions on Iran - Heryandi, Melinda Aindya; Sinulingga, Anita Afriani; Jamilah, Maryam (JLAST : Journal of Law and Social Transformation, 2023)
As a strong ally of the US, Turkey was subject to economic penalties in May 2018 for its continued imports of Iranian oil. Turkey delayed deciding whether to import Iranian oil despite this pressure. The purpose of this study is to examine Turkey's foreign policy about the importation of Iranian oil in 2018. The study uses a qualitative method with an explanatory analysis approach, drawing on the foreign policy theories of Morgan and Palmer, which highlight the objectives of proaction and security. The results show that Turkey's foreign policy goals are more proactive due to two major variables. First, Turkey and the United States do not work together well. Second, Turkey's proaction-oriented foreign policy is influenced by its capabilities, which include military might, alternative alliances, influence both regionally and internationally, and bargaining power. Turkey forms new alliances with Iran, China, and Russia, primarily concentrating on deepening its relationship with Russia. Furthermore, Turkey has a great deal of regional and global influence, as seen by its mediating role in the Syrian Israeli crisis in 2011. Turkey's foreign policy dynamics are further emphasized by its negotiating stance with the United States over the Incirlik zone. In conclusion, Turkey's strategic negotiating positions, alliance preferences, and regional and global capacities all influence its complex foreign policy strategy.